2018
DOI: 10.3390/su10010152
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Organic Carbon Storage in Vegetable Farms Using Different Farming Practices in the Kanto Region of Japan

Abstract: Agricultural fields can store substantial amounts of atmospheric carbon in the soil. In 2011, the Environmentally Friendly Farming Direct Payment Program (EFFDPP) began as a way to promote sustainable agriculture, but the approved methods for receiving the subsidy are limited to the use of manure and cover crops. For evaluating other options for the EFFDPP, we calculated soil carbon inputs and CO 2 emissions in four nature farming (NF) systems for comparisons with conventional farming (CF) and environmentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
1
12
0
1
Order By: Relevance
“…The distribution of total nitrogen content followed a similar trend to the TC distribution and was relatively higher in the CF+OF system than TC in the CF system (Table 5). This result is consistent with Zibilske et al [52], who reported that changes in soil organic N are often directly related to changes in soil organic C. Overall, the SOC level in Afghanistan is lower than in other Asian countries [12,53], which may be attributed to the low organic input and low rainfall in the region. In addition, the wet and dry cycles caused by intermittent irrigation might enhance soil organic matter decomposition, resulting in low TC, AC, and TN levels.…”
Section: Changes In Soil Properties By Organic Fertilizer Applicationsupporting
confidence: 88%
“…The distribution of total nitrogen content followed a similar trend to the TC distribution and was relatively higher in the CF+OF system than TC in the CF system (Table 5). This result is consistent with Zibilske et al [52], who reported that changes in soil organic N are often directly related to changes in soil organic C. Overall, the SOC level in Afghanistan is lower than in other Asian countries [12,53], which may be attributed to the low organic input and low rainfall in the region. In addition, the wet and dry cycles caused by intermittent irrigation might enhance soil organic matter decomposition, resulting in low TC, AC, and TN levels.…”
Section: Changes In Soil Properties By Organic Fertilizer Applicationsupporting
confidence: 88%
“…On the basis of the five aspects of agricultural inputs, rice cultivation, livestock and poultry farming, soil, and straw burning, some scholars have measured carbon emissions from agriculture as a whole to quantify the carbon emissions released from various processes in agricultural production [ 25 , 26 ]. Another group of scholars has estimated the agricultural carbon emissions associated with crop type and farming practices by using the plantation crop parameter estimation method for the main carbon emission sources such as fertilizers and pesticides, which are factors of agricultural inputs [ 27 , 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic and practitioner literature has favorably associated veganic approaches with various agronomic factors, including: yield, quality, nutrient cycling, soil nitrogen level, soil carbon storage, soil biology, soil organic matter, and energy inputs (Pimentel et al 2005 ; Cormack 2006 ; Hepperly et al 2006 ; Eisenbach et al 2018 ; Matsuura et al 2018 ; Eisenbach et al 2019 ; Roussis et al 2019 ; Rosato et al 2020 ; Utter and Seymour forthcoming) 3 ; sustainable agriculture or food systems (Hall and Tolhurst 2007 ; Visak 2007 ; Burnett 2014 ; Bonsall 2015 ; Hagemann and Potthast 2015 ; Hirth 2020 ; Kassam and Kassam 2021 ; Nobari 2021 ); food safety (O’Brien 1964 ; Seymour 2018a ; Alsanius et al 2019 ; Utter and Seymour forthcoming); diminished environmental impacts (Markussen et al 2014 ; Seymour 2018a ); marketing potential (Jürkenbeck et al 2019 ; Jürkenbeck and Spiller 2020 ); and “animal-friendly” (Visak 2007 ) and “post-lethal” (Mann 2020 ) agriculture. Despite the diversity of veganic methods and the ostensible benefits of veganic agriculture, there is relatively little scholarly literature on the topic , as has been noted by Hagemann and Potthast ( 2015 ), Schmutz and Foresi ( 2017 ), and Jürkenbeck et al ( 2019 ).…”
Section: Introductionmentioning
confidence: 99%